2021
DOI: 10.1186/s13148-021-01114-5
|View full text |Cite
|
Sign up to set email alerts
|

Detecting cord blood cell type-specific epigenetic associations with gestational diabetes mellitus and early childhood growth

Abstract: Background Epigenome-wide association studies (EWAS) have provided opportunities to understand the role of epigenetic mechanisms in development and pathophysiology of many chronic diseases. However, an important limitation of conventional EWAS is that profiles of epigenetic variability are often obtained in samples of mixed cell types. Here, we aim to assess whether changes in cord blood DNA methylation (DNAm) associated with gestational diabetes mellitus (GDM) exposure and early childhood grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…These genes are known markers of bone marrow hematopoietic progenitors, B lymphocytes, and lymphoid progenitor cells in blood, and the same genes are also markers of specific glial cells of the brain [34]. These findings suggested that DNA methylation differences in adult blood have significant concordance with fetal brain, a finding that is consistent with the idea of blood cells as keepers of epigenetic memory of early-life development [35,36]. We also used gene expression data of developing fetal brain of pig from our earlier study [11] to understand effect of the common methylations on gene regulation of brain during fetal development.…”
Section: Discussionsupporting
confidence: 69%
“…These genes are known markers of bone marrow hematopoietic progenitors, B lymphocytes, and lymphoid progenitor cells in blood, and the same genes are also markers of specific glial cells of the brain [34]. These findings suggested that DNA methylation differences in adult blood have significant concordance with fetal brain, a finding that is consistent with the idea of blood cells as keepers of epigenetic memory of early-life development [35,36]. We also used gene expression data of developing fetal brain of pig from our earlier study [11] to understand effect of the common methylations on gene regulation of brain during fetal development.…”
Section: Discussionsupporting
confidence: 69%
“…As a primary step to explore cell-type specific changes in DNAm with GA, we used the interaction-based algorithm CellDMC that has been validated in several EWAS datasets and data in which the actual cell-type composition is known 24 , 33 , 34 . We identified 2330 differentially methylated CpGs associated with GA, with an overwhelming number of the significant CpGs confined to nRBCs (2030 CpGs linked to 2836 genes).…”
Section: Discussionmentioning
confidence: 99%
“…However, the similar lifestyles, cultural backgrounds, and socioeconomic status of the participants; the high-quality control procedures; and the Houseman regression calibration method, which accounts for different cell-type compositions, can reduce bias. The epigenetic effect of Cr should be further explored in different cell types because DNA methylation might be specific to certain cell types ( Lu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%